Gei, Gei, Gei and Gei, interaction between lexical semantics and syntactic position of Gei in mandarin Chinese - Xinyue YU; Xiaoshi Hu (2014)
<embed height="0" type="application/thunder_download_plugin" width="0"></embed> <embed height="0" type="application/thunder_download_plugin" width="0"></embed> <embed height="0" type="application/thunder_download_plugin" width="0"></embed> <embed height="0" type="application/thunder_download_plugin" width="0"></embed> <embed height="0" type="application/thunder_download_plugin" width="0"></embed>